Tathwîr Qamûs al-Jayb li Thullâb bi Madrasah al-Ibtidâiyyah - Triyana, Arum Agus; Erlina, Erlina; Koderi, Koderi; Anis, Indah Khoirul; Nurudin, M (Jurnal Internasional Pendidikan Bahasa Arab, 2023)
This study aims to produce a product in the form of an Arabic-Indonesian dictionary. The role of the media is very important in learning, namely to increase student motivation, arouse enthusiasm for learning and can liven up an effective learning atmosphere. Then researchers are interested in compiling a pocket dictionary, with the hope that the existence of this Arabic-Indonesian pocket dictionary product allows students to study independently and can help them to more easily understand the material. The formulation of the problem in this study is how is the preparation of the Arabic-Indonesian pocket dictionary as a supporter of the Arabic-Madrasah Ibtidaiyah book. Furthermore, this research is a research and development developed by Reiser and Mollenda in 1990 or better known as the ADDIE model with the stages, namely analysis, design, development, implementation and evaluation. The data collection instrument used was a questionnaire. While the technical analysis of the data used in the form of material expert validation sheets, design expert validation sheets, teacher and student response questionnaires.The results of this study are proven by the value of the validation results by material experts, namely 89% and the validation results by learning design experts, namely 86%. The value of the educators is 86% and the average value of the students' pre-test is 54.16 and the post-test score is 84.16. So it was concluded that the preparation of the Arabic-Indonesian pocket dictionary as a support for the Arabic book of Madrasah Ibtidaiyah was very feasible to use.